The Biogeographical Distribution of Soil Bacterial Communities in the Loess Plateau as Revealed by High-Throughput Sequencing - Liu, Dong; Yang, Yang; An, Shaoshan; Wang, Honglei; Wang, Ying (Frontiers in Microbiology, 2018)
The rigorous environmental stress of the severely eroded Loess Plateau may have promoted specific soil bacterial communities in comparison to other eco-environmental regions. In order to unmask the bacterial diversity and most influential environmental parameters, Illumina MiSeq high throughput sequencing of 16S rRNA from 24 representative soil samples collected across south-east to north-west transect of the Loess Plateau in northern Shaanxi, China was conducted. This high-throughput sequencing revealed a total of 1,411,001 high quality sequences that classified into 38 phyla, 127 classes, >240 orders, and over 650 genera, suggesting a high bacterial richness across the Loess Plateau soils. The seven dominant groups were: Proteobacteria, Actinobacteria, Acidobacteria, Planctomycetes, Gemmatimonadetes, Chloroflexi, and Verrucomicrobi (relative abundance of >5%). Increasing/decreasing soil pH and geographic longitudinal distance correlated significantly with increasing/decreasing bacterial richness and diversity indices. Pairwise correlation analysis showed higher bacterial diversity at longitudinal gradients across 107°39′-109°15′ (south-east to north-west) in our studied Chinese loess zone. Variation partitioning analysis indicated significant influence of soil characteristics ( 40.4%) than geographical distance (at a landscape scale of 400 km) that was responsible for 13.6% of variation in bacterial community structure from these soils. Overall, contemporary soil characteristics structure the bacterial community in Loess Plateau soil to a greater extent than the spatial distances along the loess transect.